2010
DOI: 10.1121/1.3284546
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral audiogram of whitetail deer (Odocoileus virginianus)

Abstract: The behavioral audiograms of two female white-tailed deer (Odocoileus virginianus) were determined using a conditioned-suppression avoidance procedure. At a level of 60dB sound pressure level, their hearing range extends from 115Hzto54kHz with a best sensitivity of −3dB at 8kHz; increasing the intensity of the sound extends their hearing range from 32Hz (at 96.5dB) to 64kHz (at 93dB). Compared with humans, white-tailed deer have better high-frequency but poorer low-frequency hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…There is a remarkable similarity between alpacas and the two species of deer for which data are available-the New World white-tailed deer and the Old World reindeer (Fig. 7) (Flydal et al, 2001;Heffner and Heffner, 2010). Between 1 and 16 kHz the hearing of these three species is virtually identical, including the reduced sensitivity at 2 kHz.…”
Section: A Audiogrammentioning
confidence: 85%
See 2 more Smart Citations
“…There is a remarkable similarity between alpacas and the two species of deer for which data are available-the New World white-tailed deer and the Old World reindeer (Fig. 7) (Flydal et al, 2001;Heffner and Heffner, 2010). Between 1 and 16 kHz the hearing of these three species is virtually identical, including the reduced sensitivity at 2 kHz.…”
Section: A Audiogrammentioning
confidence: 85%
“…The audiograms of cattle and pigs are illustrated for comparison to show the range of sensitivities in artiodactyls. Alpaca auditory sensitivity (bold black line), pig (Heffner and Heffner, 1990), cattle (Heffner and Heffner, 1983), reindeer (Flydal et al, 2001), and white-tailed deer (Heffner and Heffner, 2010). …”
Section: B Sound-localization Acuity (Minimum Audible Angle)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, deer whistles are purported to produce ultrasonic sounds audible to deer but not humans. However, physiological investigations, and a single small‐scale behavioral study ( n = 2) suggest that these frequencies fall outside the hearing range of deer (Valitzski et al 2009, Heffner and Heffner 2010). Thus, it is not surprising that numerous studies have shown that mitigation devices reliant on deer vision are ineffective at reducing DVCs (Reeve and Anderson 1993, D'Angelo et al 2006, Blackwell and Seamans 2008) or altering deer behavior (Waring et al 1991; Ujvári et al 1998; VerCauteren et al 2003, 2006; D'Angelo et al 2006).…”
mentioning
confidence: 98%
“…Various scientific studies have focused on strategies to minimize deer–vehicle collisions (DVCs) and to reduce damage to cultivated plants (VerCauteren et al 2003, 2006; Blackwell and Seamans 2008). However, despite some understanding about white‐tailed deer visual and auditory physiology (Jacobs et al 1994; D'Angelo et al 2007, 2008), little research has confirmed how deer perceive their environment through sight and sound (Zacks and Budde 1983, Zacks 1985, Birgersson et al 2001, VerCauteren and Pipas 2003, Heffner and Heffner 2010). Even then, interpretation of these studies is difficult due to small sample size and the cognition systems of animals (Jacobs 1993, VerCauteren and Pipas 2003).…”
mentioning
confidence: 99%